Penerapan Media PENCILS dalam Meningkatkan Pemahaman Siswa Pada Materi Rangkaian Hambatan Listrik - Herry Suryanto (SEJ (Science Education Journal), 2017)
This study is class action research conducted at class A of 9th grade in SMPN 1 Prambon, Kabupaten Sidoarjo. Based on preliminary study, students still found some difficulties to solve the problem about Electrical Series. This was proven from their average score of test on this topic that is 73,19, which is still lower than KKM score that is 76. This research aimed to analyze the effect of using PENCILS media on increasing students’ understanding about Electrial Series topic. PENCILS media is software application in computer. The analysis result in the first cycle, from 36 students, 21 of them had score lower than KKM. In the second cycle, learning process used PENCILS as learning media to facilitate students’ difficulty. The result of analysis data in the second cylce showed that only 6 students had score lower than KKM and the average score of test was 77,37. The third cycle was conducted to ensure that the score obtained is stable. Based on the result of data analysis in the last cycle indicated that only 3 students had score lower than KKM and the average score of test was 78,75. In conclusion, the PENCILS media can be effectively used to improve students’ understanding on the topic of Electrical Series.